Video documental sobre el dialogo de saberes del científico indígena Miguel Ángel Gualoto. - Luna Cevallos, Estefanía Elizabeth (2016)
The documentary “I´m Gualoto” was created in Quito - Ecuador and the objective was investigate the existence of the dialogue of knowledge in the investigations that doing Miguel Ángel Gualoto, especially on his research: Bioremediation of soils with hydrocarbons and Antarctic microorganisms at the scientific station Pedro Vicente Maldonado. Miguel Angel Gualoto shares about his childhood in Ecuador, his youth in the former Soviet Union, his illness that will accompany him throughout his life, his work in Antarctica; the moments he spends with his family and the denigration, stigmas and stereotypes that he had faced throughout this journey. The methodology contained as a qualitative approach, which ranged from a bibliographic theoretical field and even to a research field (interviews) which inspires to check if exist or not a dialogue of knowledge in Miguel Ángel Gualoto. This investigation, besides showing if the dialogue of knowledge is important in the projects of investigation, it is part of a scientific publication that aims and highlights the work done by an Ecuadorian, It is a way to highlight the activities carried out in our country as a fundamental part of our development.